If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m = 2m + 6 Reorder the terms: m = 6 + 2m Solving m = 6 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. m + -2m = 6 + 2m + -2m Combine like terms: m + -2m = -1m -1m = 6 + 2m + -2m Combine like terms: 2m + -2m = 0 -1m = 6 + 0 -1m = 6 Divide each side by '-1'. m = -6 Simplifying m = -6
| 15x^2+40x-400=0 | | 9f-4=f+19 | | 222-544= | | 10=-16/r+8 | | 15/e-1=-46 | | 6x-8=7+3 | | 4/x=-32 | | -56/m=-2 | | 5=-25/x | | x/27-32=-4 | | j/-8-13=-35 | | 2-X*66=h | | -30=l/-5-24 | | k/6-16=4 | | 10=c/-4-2 | | 684/18=j/-21 | | 4v+12=48 | | -768/32=p/5 | | b-6a= | | 1/2h=-38 | | -41=-1/3y | | -1000/25=u/-9 | | 7x+7y=-91 | | 5x+8y=-92 | | -12=t/-15 | | x-2/3+x+1/2=4 | | -8=w/12-10 | | y^3+2y^2-5y-6=0 | | z/10-3=5 | | f/12+58=-12 | | 21/4+1/18 | | n/-8+9=-23 |